Top Management Team Characteristics, Overconfidence, and Financial Asset Allocation - Rangkun Qi (Amfiteatru Economic)
The large-scale allocation of financial assets by enterprises indicates economic financialization at the micro-level. Scholars have extensively discussed its influencing factors, but most are based on the traditional assumption of “rational people.” The annual data of listed companies in China for the period 2008 to 2020 was used to explore how the characteristics of the top management team (TMT) affect a company’s financial asset allocation, considering that “people are imperfectly rational and heterogeneous” as a research perspective. The mediating effect and the influence of overconfidence on TMT’s characteristics affecting financial asset allocation were analyzed through a mediation model, a two-way fixed effects model, and the Logit method. Results reveal that TMT’s characteristics, such as gender, age, tenure, education, finance, and overseas experience, have a differentiated influence on financial asset allocation. The transmission mechanism of overconfidence in this process is more complicated, with a partial mediating effect and a suppressing effect. Conclusions provide managerial implications for the government, companies, and executives in carrying out collaborative operations and jointly promoting the financial services for the entity.